Pertanggungjawaban Pelaku Usaha Atas Overclaim di Kandungan Skin Care pada Produk Retinol Serum ElsheSkin - Made Arsia Luna Tantra (Aliansi: Jurnal Hukum, Pendidikan dan Sosial Humaniora, 2025)
The practice of overclaiming in the skincare industry, particularly through e-commerce platforms, has emerged as a critical concern in the realm of consumer protection law. Misleading product claims, especially regarding active ingredients such as retinol, can not only compromise consumer trust but also pose health risks. This study aims to analyze the legal responsibility of business actors in cases of exaggerated product claims, with a focus on the ElsheSkin case, in which the retinol content was scientifically proven to differ significantly from what was stated on the product label. Employing a juridical-normative and descriptive-analytical approach, this study uses secondary data derived from relevant legislation, expert commentary, regulatory standards, and digital media content. The findings indicate that ElsheSkin’s mislabeling constitutes a violation of the principle of transparency and the right of consumers to obtain accurate product information as regulated in Indonesian consumer protection law, particularly Law No. 8 of 1999. Despite the violation, ElsheSkin displayed a degree of legal and ethical responsibility by conducting a product recall, offering compensation to affected consumers, issuing a public apology, and initiating improvements to internal quality control mechanisms. The case underscores the urgent need for stronger regulatory oversight in the digital marketplace, especially in the skincare sector, where scientific claims can be easily manipulated for marketing gain. It also emphasizes the importance of enhancing public awareness and education regarding product ingredients and their actual effects. In conclusion, while business actors are legally bound to ensure the accuracy of product information, there must also be a collaborative effort between regulators, companies, and consumers to create a more transparent and trustworthy digital commercial environment.